How do explicitly stated hospital trust values relate to their CQC ratings?. Issue 2 (26th March 2018) - Hamnett, Nathan; Patel, Naomi; Nelson, Kathryn; Harrison, Tom; White, Nicholas
Abstract : Introduction: For National Health Service (NHS) Trusts in the process of setting internal organisational values, it would be useful to see if there was a correlation between certain organisational values and Care Quality Commission (CQC) ratings to enable quality improvement. Methods: To examine this, we identified the CQC ratings of the NHS England provider trusts and identified and listed the trust's values. These values were then categorised and a comparison made of well-performing and underperforming trusts. Results: A total of 43 different values were identified, with a total of 800 values being used across all 188 trusts. In the reviewed hospitals, a broad range of values were found with some not meeting common definitions of what a value is. All trusts included some aspect of behaviour in their values. Conclusion: Well-performing hospitals are more likely to be open and honest with aspirational values, whereas those which are not are more likely to be focused on day to day service delivery with operational or proscriptive values. There was considerable variation from the published NHS constitution values with outstanding and good trusts having more variance from the values in the NHS constitution than trusts rated requiring improvement or inadequate.